Winter Dynamics in an Epishelf Lake: Quantitative Mixing Estimates and Ice Shelf Basal Channel Considerations. Issue 9 (30th August 2021) - Bonneau, Jérémie; Laval, Bernard E.; Mueller, Derek; Hamilton, Andrew K.; Friedrichs, Andrew M.; Forrest, Alexander L.
Abstract: Milne Ice Shelf is located at the mouth of Milne Fiord (82.6°N, 81.0°W), on Ellesmere Island, Nunavut. This floating ice feature is attached to both sides of the fjord. During the melt season, the ice shelf acts as a floating barrier preventing surface runoff in Milne Fiord from flowing freely to the ocean. This results in a permanent layer of freshwater that floats on top of the seawater of the fjord, commonly known as an epishelf lake. Few studies address the physical characteristics of epishelf lakes. Here, winter data from a mooring installed in Milne Fiord epishelf lake during 2011–2019 is analyzed in the framework of a one‐dimensional model in order to study mixing in the upper water column and infer the characteristics of a basal channel in the ice shelf. The results show that vertical mixing rates are higher in the epishelf lake than in the seawater below. Estimation of the Richardson number using a geostrophic balance approach reveals that enhanced mixing in the epishelf lake is associated with horizontal temperature gradients. In contrast to most studies on basal channels in Greenland and Antarctica, the results presented here show the basal channel of Milne Ice Shelf is apparently not evolving (melting) rapidly. Plain Language Summary: An ice shelf is a thick, perennial floating sheet of ice attached to the land. At the mouth of Milne Fiord, on the northern coast of Ellesmere Island, is Milne Ice Shelf. The Milne Ice Shelf is attached to the land on both sides of the fjord and acts like a floating barrier preventing fresh meltwater from the Milne Fiord watershed from directly flowing out to the ocean. This creates a layer of freshwater floating on top of the seawater, which is called an epishelf lake. Epishelf lakes are rarely studied and little is known about these unique polar features. In this study, we use field observations and a numerical model to conclude that there is more mixing in the epishelf lake than in the seawater below. Moreover, we suggest that most of the water flowing out of the epishelf lake follows a channel under the ice shelf and that this channel has not experienced substantial submarine melting from 2011 to 2019. This result contradicts most studies of basal channels as these ice features are generally thought to be areas of enhanced submarine melt. Key Points: A one‐dimensional model is used to analyze 8 years of winter mooring data of the upper water column in a perennially ice‐covered fjord Mixing is more pronounced in the isolated freshwater layer (epishelf lake) than in the seawater below Epishelf lake water exits the fjord through a basal channel under the ice shelf. The channel is apparently not evolving rapidly